Dampak Penetapan Batas Umur Perkawinan Berdasarkan Undang-Undang Nomor 16 Tahun 2019 Terhadap Dispensasi Kawin Di Kabupaten Purbalingga - Anisa Nur Sagita; Marsitiningsih Marsitiningsih (PSHPM Untag Semarang, 2025)
Marriage in Indonesia is governed by Law Number 16 of 2019, which sets the minimum legal age for marriage at 19 years for both men and women. Despite this regulation, the marriage dispensation continues in Purbalingga Regency, influenced by social, economic, and cultural factors, including premarital pregnancy and social pressure. Data indicate a decline in the number of marriage dispensation casesfrom 442 in 2022, to 398 in 2023, and 321 in 2024. This legal age stipulation aims to protect children’s rights and improve the quality of education and reproductive health among adolescents. This study analyzes two key aspects: the factors considered by judges when deciding on marriage dispensation requests and the impact of the legal age provision on early marriage practices. The research employs a normative juridical approach supported by field data. Findings reveal that judges at the Purbalingga Religious Court consider the emotional readiness of the prospective spouses, the reasoning behind the request, and the social implications of the decision. Furthermore, the age stipulation has significantly reduced instances of early marriage, with the expectation that individuals who marry at a later age possess greater emotional maturity. This study underscores the importance of child protection and public awareness regarding the appropriate legal age for marriage.